Analysis of fluency, space, weight and time in the walking of the Physical Education teacher during classes - Sandra Barbosa da Costa; Pierre Normando Gomes-; Danielle Menezes de Oliveira Gonçalves (Desafio Singular, 2017)
This study analyzed the pedagogical intentionality expressed in the teacher's walk in physical education classes. The data collection was carried out during seven months of direct observation of teachers with different past teaching experience (5 years, more than 10 years and more than 20 years), different genders, different schools and different class situations. In a descriptive and qualitative research, the Laban Movement Analysis was used to describe the walk of teachers in its expressive qualities, comprising the combination of four factors (fluency, space, weight and time) as well as the Pedagogy of Corporeality to analyze the creation of educational movement. During the identification of the three conditions during class (conducting, organizing and enforcing), it was observed that only in the vigorous way of walking to enforce the students, a greater variability in the combination of factors was present. The older group of teachers demonstrated the incorporation of knowledge experience in an integrative pedagogical intentionality.